A Review of Advances in Cold Spray Coating Process - Saikumar Chalivendra (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Cold spray coating technique gives rise to a new technique of applying high performance coatings to different substrates. Not the same as more typical thermal spraying methods which ionize materials and melt them before spraying them at the surface of the substrate at several hundred degrees, it involves the use of a high-pressure gas to propel powdered material towards a surface at supersonic velocities and create robust and firm mechanical bonds that do not require the application of heat. This process has drastically developed to the extent of material choice, quality coatings, and commercial uses. However, there are still some problems which have to be solved, namely the preparation of the substrate, the choice of the material and the cost of equipment. This paper examines the most recent innovations in the cold spray technique, its uses, advantages and limitations, and the future prospects of this pioneering coating method.
Keywords: Spray Coating; Thermal; Gun; Helium